Hubungan Self-Esteem dan Impulsive Buying pada Produk Skincare Pengikut Akun Mention Confession di Twitter - Michelle Thalia Roteng; Yudi Tri Harsono (Universitas Negeri Malang, 2022)
With the development of beauty standards in Indonesia, the popularity of skincare and its purchasing interest has also increased. Technological advancements have made it easier to share and receive information related to skincare products, which influences their purchasing decisions, such as through the mention confession account on Twitter. There are various types of mentions confession account created for different discussion topics and information, the one that relevant with skincare products is @ohmybeautybank. This study aimed to explore the relationship between self-esteem and impulsive buying of skincare products among followers of the mention confession account on Twitter. Data was collected using questionnaire using incidental sampling with the following criteria: 1) followers of the @ohmybeautybank Twitter account, and 2) buyers and users of skincare products. A total of 201 respondents obtained. Data were analyzed using Spearman Rank correlation with SPSS Statistics version 25 for Windows. The results showed that 1) there was a significant negative correlation between the self-liking dimension and impulsive buying of skincare products among followers of the @ohmybeautybank account on Twitter, and 2) there was a significant negative correlation between the self-competence dimension and impulsive buying of skincare products among followers of the @ohmybeautybank account on Twitter. AbstrakSeiring dengan berkembangnya standar kecantikan di Indonesia, popularitas skincare dan minat pembeliannya juga semakin meningkat. Perkembangan teknologi kemudian memberikan kemudahan bagi individu dalam menyebarkan dan menerima informasi terkait produk skincare yang kemudian berpengaruh dalam pembelian, salah satunya melalui akun mention confession di Twitter. Terdapat beragam jenis mention confession yang dibuat untuk topik diskusi dan informasi yang berbeda-beda, terkait produk skincare akun yang berkaitan adalah akun @ohmybeautybank. Penelitian ini bertujuan untuk melihat hubungan antara self-esteem dan impulsive buying pada produk skincare pengikut akun mention confession di Twitter. Data dikumpulkan menggunakan kuesioner dengan teknik incidental sampling berdasarkan pada kriteria berikut, 1) pengikut akun Twitter @ohmybeautybank, dan 2) pembeli dan pengguna produk skincare. Dari penyebaran kuesioner didapatkan sebanyak 201 responden. Data dianalisis menggunakan teknik korelasi spearman rank dengan bantuan SPSS Statistics versi 25 for windows. Hasil penelitian menunjukkan bahwa, 1) terdapat hubungan negatif yang signifikan antara dimensi self-liking dan impulsive buying pada produk skincare pengikut akun mention confession @ohmybeautybank di Twitter, dan 2) terdapat hubungan negatif signifikan antara dimensi self-competence dan impulsive buying pada produk skincare pengikut akun mention confession @ohmybeautybank di Twitter.